2005
DOI: 10.3349/ymj.2005.46.1.173
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pulmonary Cryptococcosis with Non-Small Cell Lung Cancer in Idiopathic CD4+ T-Lymphocytopenia

Abstract: Cryptococcus neoformans commonly causes opportunistic infections in immunocompromised patients, especially in patients with AIDS. CD4+ T-lymphocytopenia in AIDS indicates an increased risk of opportunistic infection and a decline in immunological function. Idiopathic CD4 T-lymphocytopenia (ICL) is characterized by depletions in the CD4+ T-cell subsets, without evidence of HIV infection. Immunodeficiency can exist in the absence of laboratory evidence of HIV infection, and T-cell subsets should be evaluated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Only English language papers were reviewed. We found 258 cases diagnosed with ICL in 143 published papers[134567891011121314151617181920212223242526272829303132333435363738394041424344454647484950515253545556575859606162636465666768697071727374757677787980818283848586878889909192939495969798…”
Section: Methodsmentioning
confidence: 99%
“…Only English language papers were reviewed. We found 258 cases diagnosed with ICL in 143 published papers[134567891011121314151617181920212223242526272829303132333435363738394041424344454647484950515253545556575859606162636465666768697071727374757677787980818283848586878889909192939495969798…”
Section: Methodsmentioning
confidence: 99%
“…Our patient denied an exposure history of bird secretions, dust and pollen. Previous studies have reported that T-cell-mediated immune dysfunction often occurs in patients with cancer after chemotherapy, who are susceptible to pulmonary cryptococcosis [4,5]. We believe that surgery for such patients is a more appropriate choice, at least in some cases, which could also help attain correct diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 93%
“…We believe that the condition of our patient meets the diagnostic criteria for ICL as he had no evidence of HIV infection and had never received immunosuppressive drugs and his CD4+ T-lymphocyte count was below 300 cells/mm 3 during the long follow-up period. Further, [8][9][10]. Still, the optimal treatment and prophylaxis for OIs in patients with ICL remain to be defined.…”
Section: Discussionmentioning
confidence: 99%